English for tour guide program to improve English Skills of tour guides in Trenggalek’s Tourist Villages - Dwi Wahyuningtyas; Ria Arista Asih; Dessy Maeyangsari; A. R. Alyaa' Chiquita Fairuzara; Fredik Yunior Heuvelman; Roro Millatu Al-Ghaniy (Journal of Community Service and Empowerment, 2022)
Trenggalek is one of the potential regencies in East Java, with many beautiful tourist destinations. Realizing this fact, the government of Trenggalek has set a target to develop 100 tourist villages in Trenggalek by 2024. Tourist villages are now becoming one of the main attractions in Trenggalek. To make the villages more known and visited by tourists, some support is needed, one of which is the involvement of tour guides skilled in using English. Therefore, the community service team from UPN "Veteran" Jawa Timur under the scheme PIKAT (Pemanfaatan Ipteks Bagi Masyarakat = Utilization of Science and Technology for Society) held an English for Tour Guide program in Pandean Village, Dongko Sub-district, Trenggalek. Supported by the Department of Tourism and Culture of Trenggalek. This program has been held since July and is still running.  The service program consists of three main activities, namely: (1) preparation, debriefing, and pre-departure; (2) implementation; and (3) evaluation. The tour guides joined and attended the program enthusiastically. They were actively involved in the discussions, sharing sessions, and role-plays. It is expected that this program can be impactful for tour guides in tourist villages in Trenggalek and can be extended in a broader scope in the future. In addition, more tourists are interested in visiting Trenggalek, from East Java and around Indonesia.